1972
DOI: 10.1037/h0033629
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of induced amnesia in short-term memory.

Abstract: In two experiments, 5s were required to free recall lists of line drawings of common objects. Some of the lists contained a critical item, a photograph of nudes, in place of the middle item. In addition, instructions regarding rehearsal, rate of presentation of list items, and exposure duration of the critical item were varied. The critical item produced' a von Restorff effect accompanied by substantial anterograde and retrograde induced amnesia. Instructions minimizing rehearsal had no effect on retrograde am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 8 publications
5
60
0
Order By: Relevance
“…These typically either involve sequences with just one arousing item (Hurlemann et al, 2005;Strange et al, 2003;Schmidt, 2002;Erdelyi & Blumenthal, 1973;Detterman & Ellis, 1972;Ellis et al, 1971;Runcie & O'Bannon, 1977;MacKay et al, 2004) or rapid serial visual presentation without responses required from the participants until the end of the list (Hadley & MacKay, 2006). The current findings suggest that this type of arousal-based interference seen for item memory will not extend to item-location conjunction memory.…”
Section: How These Findings Contrast With Other Effects Of Emotionmentioning
confidence: 55%
See 1 more Smart Citation
“…These typically either involve sequences with just one arousing item (Hurlemann et al, 2005;Strange et al, 2003;Schmidt, 2002;Erdelyi & Blumenthal, 1973;Detterman & Ellis, 1972;Ellis et al, 1971;Runcie & O'Bannon, 1977;MacKay et al, 2004) or rapid serial visual presentation without responses required from the participants until the end of the list (Hadley & MacKay, 2006). The current findings suggest that this type of arousal-based interference seen for item memory will not extend to item-location conjunction memory.…”
Section: How These Findings Contrast With Other Effects Of Emotionmentioning
confidence: 55%
“…A number of studies have shown that arousing stimuli can interfere with memory for spatially or temporally nearby neutral items (Bornstein, Liebel, & Scarberry, 1998;Detterman & Ellis, 1972;Ellis et al, 1971;Erdelyi & Blumenthal, 1973;Hadley & MacKay, 2006;Hurlemann et al, 2005;Johnson et al, 2005;MacKay et al, 2004;Miu, Heilman, Opre, & Miclea, 2005;Runcie & O'Bannon, 1977;Schmidt, 2002;Strange, Hurlemann, & Dolan, 2003). Although some of these studies used very rapid presentation, item memory impairment for temporally adjacent items also has been found with up to three or four seconds between the arousing and neutral items (Detterman & Ellis, 1972;Hurlemann et al, 2005;Runcie & O'Bannon, 1977) and sometimes even for items appearing six seconds after an arousing item (Schmidt, 2002). However, memory for contextual information was not tested in any of these studies, so it is not clear whether interference from adjacent emotionally arousing items also impairs binding of contextual features to neutral items.…”
mentioning
confidence: 99%
“…Requestsfor reprints should be sent to Sven-Ake Christianson, Department of Psychology, University of Umea, S-90247 Urnea, Sweden. 1973, Detterman, 1976, Detterman & Ellis, 1972, Ellis, Detterman, Runcie, McCarver, & Craig, 1971, and Tulving, 1969. Second, the critical event usually employed in the laboratory to induce amnesia is not really a traumatic event.…”
mentioning
confidence: 99%
“…No decrease in recall of the immediately following item (IFI) to the HPI was observed, which was offered as additional support for his assumptions. Detterman and Ellis (1972) found that instructions to minimize rehearsal had no effect on retrograde amnesia. In addition, longer durations of the HPI increased the observed retrograde amnesia.…”
mentioning
confidence: 99%
“…Saufley and Winograd (1970) demonstrated the same results without giving subjects special instruction to remember the critical item. Detterman and Ellis (1972) and Ellis, Detterman, Runcie, McCarver, and Craig (1971) showed that a von Restorff effect and retrograde amnesia could be produced in a somewhat different manner. Photographs of nude males and females were placed within lists of common line drawings.…”
mentioning
confidence: 99%